Modern aspects of pharmaceutical services research in Ukraine - Mahanova, T. V.; Tkachenko, N. О.; Ткаченко, Наталя Олександрівна; Маганова, Тамара Валеріївна (Запорізький державний медико-фармацевтичний університет, 2023)
Aim. Study and systematization of information about the possible component composition of a pharmaceutical service for its subsequent implementation in a comprehensive assessment of the composition of a pharmaceutical service based on expert assessment and discrete choice methods.
Keywords: тези доповідей